A dual-branch deep learning model based on fNIRS for assessing 3D visual fatigue - Wu, Yan; Mu, TianQi; Qu, SongNan; Li, XiuJun; Li, Qi (Frontiers in Neuroscience, 2025)
IntroductionExtended viewing of 3D content can induce fatigue symptoms. Thus, fatigue assessment is crucial for enhancing the user experience and optimizing the performance of stereoscopic 3D technology. Functional near-infrared spectroscopy (fNIRS) has emerged as a promising tool for evaluating 3D visual fatigue by capturing hemodynamic responses within the cerebral region. However, traditional fNIRS-based methods rely on manual feature extraction and analysis, limiting their effectiveness. To address these limitations, a deep learning model based on fNIRS was constructed for the first time to evaluate 3D visual fatigue, enabling end-to-end automated feature extraction and classification.MethodsTwenty normal subjects participated in this study (mean age: 24.6 ± 0.88 years; range: 23–26 years; 13 males). This paper proposed an fNIRS-based experimental paradigm that acquires data under both comfort and fatigue conditions. Given the time-series nature of fNIRS data and the variability of fatigue responses across different brain regions, a dual-branch convolutional network was constructed to separately extract temporal and spatial features. A transformer was integrated into the convolutional network to enhance long-range feature extraction. Furthermore, to adaptively select fNIRS hemodynamic features, a channel attention mechanism was integrated to provide a weighted representation of multiple features.ResultsThe constructed model achieved an average accuracy of 93.12% within subjects and 84.65% across subjects, demonstrating its superior performance compared to traditional machine learning models and deep learning models.DiscussionThis study successfully constructed a novel deep learning framework for the automatic evaluation of 3D visual fatigue using fNIRS data. The proposed model addresses the limitations of traditional methods by enabling end-to-end automated feature extraction and classification, eliminating the need for manual intervention. The integration of a transformer module and channel attention mechanism significantly enhanced the model’s ability to capture long-range dependencies and adaptively weight hemodynamic features, respectively. The high classification accuracy achieved within and across subjects highlights the model’s effectiveness and generalizability. This framework not only advances the field of fNIRS-based fatigue assessment but also provides a valuable tool for improving user experience in stereoscopic 3D applications. Future work could explore the model’s applicability to other types of fatigue assessment and further optimize its performance for real-world scenarios.